2019
DOI: 10.1002/jcp.29188
|View full text |Cite
|
Sign up to set email alerts
|

miR‐122‐5p promotes aggression and epithelial‐mesenchymal transition in triple‐negative breast cancer by suppressing charged multivesicular body protein 3 through mitogen‐activated protein kinase signaling

Abstract: Triple-negative breast cancer (TNBC) is highly metastatic and frequently has a poor prognosis. The lack of comprehension of TNBC and gene therapy targets has led to limitedly effective treatment for TNBC. This study was conducted to better understand the molecular mechanism behind TNBC progression, and to find out promising gene therapy targets for TNBC. Herein the influence of miR-122-5p's binding charged multivesicular body protein 3 (CHMP3) 3′-untranslated region (3′-UTR) on in TNBC cells was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…In breast cancer, hsa-miR-122 has different expression patterns according to the subtype [ 56 ]. In addition, miR-122 promotes aggression and epithelial-mesenchymal transition in TNBC [ 57 ] and cell survival in radio-resistance cells [ 58 ]. High plasma miR-122 levels have been detected in AFP-producing gastric cancer [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, hsa-miR-122 has different expression patterns according to the subtype [ 56 ]. In addition, miR-122 promotes aggression and epithelial-mesenchymal transition in TNBC [ 57 ] and cell survival in radio-resistance cells [ 58 ]. High plasma miR-122 levels have been detected in AFP-producing gastric cancer [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-122-5p is encoded on chromosome 18q21.31 and is derived from the hcr gene transcript. miR-122-5p plays an important role in cell cycle regulation, cell proliferation and cell apoptosis ( Wang & Wang, 2019 ) and is associated with multiple diseases ( Wang & Wang, 2019 ; Wen et al, 2018 ; Jiang et al, 2017 ; Cortez-Dias et al, 2016 ). Previously, we analyzed the correlation between miR-122-5p and occludin protein, and the results showed that miR-122-5p was negatively correlated with occludin expression ( Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-122-5p is encoded on chromosome 18q21.31 and is derived from the hcr gene transcript. miR-122-5p plays an important role in cell cycle regulation, cell proliferation and cell apoptosis [36] and is associated with multiple diseases [36][37][38][39]. Previously, we analyzed the correlation between miR-122-5p and occludin protein, and the results showed that miR-122-5p was negatively correlated with occludin expression [40].…”
Section: Discussionmentioning
confidence: 99%